2022
DOI: 10.1111/pace.14507
|View full text |Cite
|
Sign up to set email alerts
|

Catheter ablation for persistent atrial fibrillation with left ventricular systolic dysfunction: Who is the best candidate?

Abstract: Background Tachycardia‐induced cardiomyopathy is poorly recognized pre‐ablation. It remains unclear of better patient selection and timing for catheter ablation in persistent atrial fibrillation (PerAF) with heart failure (HF). Methods Consecutive patients with PerAF and left ventricular ejection fraction (LVEF) <50% referred for AF ablation were retrospectively included. The impact of LV size, heart rate (HR), and LVEF pre‐ablation were analyzed for assessing LV systolic function recovery, defined as LVEF inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…These inconsistent results may be attributed to several factors, such as patient characteristics, HF etiology, follow-up duration, and ablation strategy. In addition, the improvement of prognosis in HF with impaired LVEF may be partially explained by the presence of tachycardia-induced cardiomyopathy, which is poorly recognized pre-ablation ( 36 ). However, it remains unclear of better patient selection and timing for RFCA in persistent AF with HF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These inconsistent results may be attributed to several factors, such as patient characteristics, HF etiology, follow-up duration, and ablation strategy. In addition, the improvement of prognosis in HF with impaired LVEF may be partially explained by the presence of tachycardia-induced cardiomyopathy, which is poorly recognized pre-ablation ( 36 ). However, it remains unclear of better patient selection and timing for RFCA in persistent AF with HF.…”
Section: Discussionmentioning
confidence: 99%
“…However, it remains unclear of better patient selection and timing for RFCA in persistent AF with HF. A recent study ( 36 ) indicated that patients with normal to moderate LV dilation, resting heart rate ≥ 80 bpm and HFmrEF may be candidates for early RFCA to achieve LVEF normalization.…”
Section: Discussionmentioning
confidence: 99%